From critical reflection to critical professional practice: Addressing the tensions between critical and hegemonic perspectives. (March 2022) - Timor-Shlevin, Shachar; Aharon, Tamar; Segev, Sharon; Mazor, Shani; Ishai, Emily
Critical reflection processes are fundamental to critical social work practice. Nevertheless, these processes have been criticized for lacking a coherent translation to direct professional practice. Existing models of critical reflection culminate in the formulation of critical professional perspectives, leaving the translation of critical perspectives into direct practice underdeveloped. This gap requires attention, specifically in the contemporary context of social services that operate under the hegemony of conservative and neoliberal discourses, which impede critical rationality and practice. Therefore, a nuanced conceptualization of the process that links critical reflection and critical practice is required. This article provides such a conceptualization by describing an undergraduate social work course that used a collaborative inquiry group to explore critical participatory practices. Building on our collaborative inquiry experiences and findings, we portray a process that included critical reflection, direct critical practice, and the development of a critical professional perspective. Based on the conceptual framework of action science, our conceptualization demonstrates how the process of addressing the tension between critical and hegemonic perspectives enables professionals to create critical practice within the hegemonic field. In this way, we provide a theoretical contribution to the construction of critical reflection models and a practical contribution to professional developmental processes that promote critical professionalism.